Phenomenology and humanistic-existencial psychotherapy - Sassenfeld Jonquera, André; Moncada Arroyo, Laura (Revista de Psicología, 2006)
This article presents some fundamental concepts of phenomenology and the phenomenological method that throw some light on psychotherapeutic practice as theoretical frame for humanistic-existential psychotherapy. To accomplish this, first the way in which humanistic existential psychotherapists understand the nucleus of the phenomenological approach is outlined and second some possible uses of phenomenology in the area of clinical theory and practice are specified.